Landboflid, paaskiønnet af det Kongl. Landhuusholdningsselskab i Aarene 1846 og 1847. - Hald, J. C. (Tidsskrift for Landøkonomi, 2018)
Landboflid, paaskiønnet af det Kongl. Landhuusholdningsselskab i Aarene 1846 og 1847.